Analisis Sebaran Pencemaran Lindi dengan Sifat Kelistrikan Konfigurasi Wenner-Schlumberger di TPA Pakusari - Amallia Rizky (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Pakusari Landfill has reached a saturation point that touches 90% full. This makes the Pakusari Landfill unable to accommodate waste continuously. The impact resulting from garbage piles causes leachate to seep into the soil so that it contaminates groundwater. Analysis of the distribution of leachate pollution is needed to interpret leachate that can contaminate the surrounding groundwater. Especially groundwater that is still used by local residents for daily needs. The purpose of this research is to determine the distribution of leachate pollution measured by the electrical properties of the Wenner-Schlumberger configuration in the north and east parts of the Pakusari Landfill. The geophysical method used is the Wenner-Schlumberger configuration. Data processing from geoelectric measurements using Res2Dinv software so that the distribution of leachate under the ground surface in the form of 2 Dimensions is obtained. The result of this study is that the resistivity value of 10 Ωm is expressed as leachate. Where in the northern part of the Pakusari Landfill dominates the quantity and contamination of leacha. This is because the measurement on track 1 is right next to the pile of garbage where there is puddles of polluted water in the rainy season at several points. This condition confirms that the low resistivity at the measurement points in the northern part is soil that absorbs the remnants of leachate contamination so that leachate tends to still accumulate in the area. Meanwhile, in the eastern part of the Pakusari Landfill, as shown by track 2 and track 3, the distribution of leachate has been seen but is still uneven. Resistivity values of less than 10 Ωm are expressed as leachate depicted in blue-green color.
Entry oleh Arif 2026 Januari 27
Keywords: Leachate; Pakusari Landfill; Wenner-Schlumberger Configuration